(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined the determinants of loan acquisition and repayment capacity among cooperative farmers benefiting from the Bank of Agriculture (BOA) loan scheme in Southwestern Nigeria. The study addressed the persistent challenge of limited access to agricultural credit and poor loan repayment performance among smallholder farmers, which continue to constrain agricultural productivity and rural economic development. A multistage sampling technique was adopted to select 344 cooperative farmer beneficiaries across the study area, while primary data were collected using a structured questionnaire. Descriptive statistics and multiple regression analysis were employed to analyze the data. The findings revealed that socio-economic characteristics significantly influenced both loan acquisition and repayment capacity among cooperative farmers. Specifically, variables such as age, educational level, household size, marital status, and farming experience showed statistically significant relationships with farmers’ ability to access and repay agricultural loans. The regression results further indicated that the explanatory variables jointly accounted for a substantial proportion of the variations in loan acquisition and repayment behaviour among the respondents. These findings underscore the importance of farmers’ demographic and socio-economic profiles in determining credit utilization outcomes and repayment sustainability. The study concludes that improving agricultural credit performance requires greater consideration of borrower-specific characteristics in credit administration. Consequently, the study recommends that the Bank of Agriculture and other agricultural lending institutions should strengthen borrower assessment frameworks by incorporating socio-economic indicators into credit appraisal, loan disbursement, and repayment scheduling mechanisms. Such measures would enhance loan accessibility, improve repayment performance, and promote sustainable agricultural financing in Nigeria.